Face Negatiation Communication of The Demokrat Party in The Koalisi Perubahan Untuk Persatuan Towards The 2024 Presidential Election - Putri, Adelia Kharisma; Abadi, Totok Wahyu (Procedia of Social Sciences and Humanities, 2024)
The Koalisi Perubahan untuk Persatuan in the 2024 Presidential Election, which is nominating Anies Baswedan as Presidential Candidate, appears to be discord. The Demokrat Party which also supported Anies had to swallow the bitter pill after AHY, which was predicted to be a party with the Mercy logo, failed to be selected by Anies as the vice presidential candidate who would accompany him in the 2024 presidential election. Unilaterally, Nasdem, who was nominating Anies as the 2024 presidential candidate, 'switched his heart' to PKB by declaring Muhaimin Iskandar as the vice presidential candidate accompanied Anies. Suddenly, this incident made the Demokrat and their cadres angry, and turned their backs on Anies. This research aims to explain the Demokrat Party's facial negotiation communication in the Koalisi Perubahan untuk Persatuan towards the 2024 Presidential Election. This qualitative research uses Stella Ting-Toomey's Facial Negotiation perspective as the theoretical basis. The primary data for this research was obtained from YouTube social media related to AHY and the Demokrat Party after the AMIN Declaration. The units of analysis used in this research are words, phrases, clauses, sentences, and images in videos of AHY and the Demokrat Party on YouTube media. The analysis technique used is descriptive. The research results show three ways in the Demokrat Party's face negotiation communication perspective, namely facework, face-threatening actions, and conflict management which tend to give in and it is better to leave the Koalisi Perubahan untuk Persatuan by looking for and finding a new more solid coalition.